BELLBOY’S ROLE IN CREATING GUEST SATISFACTION AT THE ROYAL AMBARRUKMO HOTEL YOGYAKARTA - Febriansyach, Bagas; Sulistyo, Agung; Christiatmani, M.M; Mahanani, Sumiyar; Djamil, Farah Diana; Buchori, Apit (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
As a tourism-supporting industry, the presence of hotels is able to support tourist activities. The rise of the hotel industry confirms the improvement in tourism and shows tight competition. Management competes to present attractive and quality offers as well as good service offerings. The chain of assignment policy means that the front office department has several divisions, such as the front desk agent, guest relations officer, reservations, telephone operator, and concierge. In the concierge section, there is a bellboy who is responsible for handling guest luggage. Bellboys are at the forefront of hotels when it comes to serving incoming guests. Qualitative research through a case study approach was used in this study. This research will focus on investigating the service practices of bellboy staff at the Royal Ambarrukmo Hotel Yogyakarta. Semi-structured interviews were adopted and collaborated with service dimensions including reliability, tangibleness, responsiveness, assurance, and empathy. The informants used were three bellboy staff. The concepts of Miles Huberman and triangulation are used in data analysis and validation. The Hotel Royal Ambarrukmo Yogyakarta has fully implemented the service dimensions, according to the research findings. This instrument is able to provide hotel guests with satisfaction. Furthermore, the findings of this research can be adopted as a guide for creating quality services and guest satisfaction.